Ultrasensitive Molecule Detection Based on Infrared Metamaterial Absorber with Vertical Nanogap. Issue 8 (13th May 2021) - Hwang, Inyong; Kim, Mingyun; Yu, Jaeyeon; Lee, Jihye; Choi, Jun‐Hyuk; Park, Su A.; Chang, Won Seok; Lee, Jongwon; Jung, Joo‐Yun
Abstract: Surface‐enhanced infrared absorption (SEIRA) spectroscopy is a powerful methodology for sensing and identifying small quantities of analyte molecules via coupling between molecular vibrations and an enhanced near‐field induced in engineered structures. A metamaterial absorber (MA) is proposed as an efficient SEIRA platform; however, its efficiency is limited because it requires the appropriate insulator thickness and has a limited accessible area for sensing. SEIRA spectroscopy is proposed using an MA with a 10 nm thick vertical nanogap, and a record‐high reflection difference SEIRA signal of 36% is experimentally achieved using a 1‐octadecanethiol monolayer target molecule. Theoretical and experimental comparative studies are conducted using MAs with three different vertical nanogaps. The MAs with a vertical nanogap are processed using nanoimprint lithography and isotropic dry etching, which allow cost‐effective large‐area patterning and mass production. The proposed structure may provide promising routes for ultrasensitive sensing and detection applications. Abstract : Ultrasensitive molecule detection platform for surface‐enhanced infrared absorption spectroscopy is reported. Based on using a metamaterial absorber with a 10 nm thick vertical nanogap processed via nanoimprint lithography and isotropic dry etching, a record‐high reflection difference detection signal of 36% for a 1‐octadecanethiol monolayer molecule is achieved.